Prediction of Alzheimer's disease diagnosis within 14 years through Aβ misfolding in blood plasma compared to APOE4 status, and other risk factors - Stocker, Hannah; Nabers, Andreas; Perna, Laura; Möllers, Tobias; Rujescu, Dan; Hartmann, Annette; Holleczek, Bernd; Schöttker, Ben; Gerwert, Klaus; Brenner, Hermann (Alzheimer's and dementia, 2020)
Introduction: Alzheimer's disease (AD) has a long prodromal stage and identifying high-risk individuals is critical. We aimed to investigate the ability of A beta misfolding in blood plasma, APOE4 status, and dementia risk factors to predict diagnosis of AD. Methods: Within a community-based cohort, A beta misfolding in plasma measured by immuno-infrared sensor and APOE genotypewere determined at baseline in 770 participants followed over 14 years. Associations between A beta misfolding, APOE4, and other predictors with clinical AD, vascular dementia, and mixed dementia diagnoses were assessed. Results: A beta misfolding was associated with a 23-fold increased odds of clinical AD diagnosis within 14 years. No association was observed with vascular dementia/mixed dementia diagnoses. APOE4-positive participants had a 2.4-fold increased odds of clinical AD diagnosis within 14 years. Discussion: A beta misfolding in blood plasma was a strong, specific risk prediction marker for clinical AD evenmany years before diagnosis in a community-based setting.
Gesehen am 07.07.2020